Functional analysis of the AUG- and CUG-initiated forms of the c-Myc protein. - Blackwood, E M (1994)
Activation of the c-myc proto-oncogene by chromosomal translocation or proviral insertion frequently results in the separation of the c-myc coding region from its normal regulatory elements. Such rearrangements are often accompanied by loss or mutation of c-myc exon 1 sequences. These genetic alterations do not affect synthesis of the major c-myc protein, p64, which is initiated from the first AUG codon in exon 2. However they can result in mutation or loss of the CUG codon located in exon 1 that normally serves as an alternative translational initiation codon for synthesis of an N-terminally extended form of c-Myc (p67). It has been hypothesized that p67 is a functionally distinct form of c-Myc whose specific loss during c-myc rearrangements confers a selective growth advantage. Here we describe experiments designed to test the functional properties of the two c-Myc protein forms. We introduced mutations within the translational initiation codons of a normal human c-myc cDNA that alter the pattern of Myc protein synthesis (p64 vs. p67). The functions of each of these proteins were experimentally addressed using co-transformation and transcriptional activation assays. Both the p64 and p67 c-Myc proteins were independently able to collaborate with bcr-abl in the transformation of Rat-1 fibroblasts. In addition, both the exon 1- and exon 2-initiated forms of the c-Myc protein stimulated transcription of a Myc/Max-responsive reporter construct to a similar level. Given the apparent absence of functional differences between p64 and p67, we conclude that the basis for c-Myc oncogenic activation lies primarily in the overall deregulation of its expression and not in alterations in the protein. The existence of the CUG translational initiator may reflect a mechanism for the continued synthesis of c-Myc protein under conditions where AUG initiation is inhibited.